Some Engineering Properties of Breadfruit Seed Varieties Relevant to Handling - Abodenyi, V. A.; Kaankuka, T. K.; Irtwange, S. V. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Determination of some engineering properties of two varieties of breadfruit seeds (Var. Africana and Var. Inversa) was carried out.  The initial moisture content was 6.85% and later adjusted by rewetting to 14.85%, 21.85% and 28.85% (wb). The following engineering properties, true density, bulk density, percentage porosity, specific heat capacity, terminal velocity and drag coefficient were determined. Thermal property (specific heat capacity) of the seed was determined using the calorimeter method. The aerodynamic properties (terminal velocity and drag coefficient) were also determined by using an air column made of a vertical wind tunnel in conjunction with a voltage regulator to vary the wind speed and a digital anemometer to determine the air speed. Data obtained were statistically analyzed using Minitab statistical software. The following results were obtained. The true density of Var. Africana decreased from 1033.68 kg/m3 to 842.81 kg/m3 which amounted to 18.5% decrease, while for var. Inversa it decreased from 948.38 kg/m3 to 911.89 kg/m3 amounting to 3.85% decrease as the moisture content increased from 6.85 to 28.85%. The bulk density was observed to increase linearly as the moisture content increased.  It increased from 361.239 to 408.723 kg/m3 for Var. Africana and 317.55 to 387.638 kg/m3 for Var. Inversa.   The porosity of Var. Africana ranges from 65.06% to 51.6% while for Var. Inversa it ranges from 66.5% to 57.2%.  The terminal velocity increased from 5.5 to 8.0 m/s for Var. Africana and 3.89 to 6.8 m/s for Var. Inversa respectively as the moisture content increased from 6.85 to 28.85 %.